To philosophize by dreaming, to dream by philosophizing: an encounter of children - Cunha, Edna Olimpia da; Carvalho, Waldênia Leão de (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This text is inspired by the joint work of two public institutions: State University of Rio de Janeiro and Municipal School Joaquim da Silva Peçanha, located on the outskirts of the State of Rio de Janeiro, through the continuing education and research project entitled Can philosophy be incorporated in Caxias? The public school bets on thinking. The project was initially intended to be developed only in courses for children but then it was expanded to courses for young people and adults. We address the possible relation between the establishment and the expansion of the philosophical project and children’s affirmation power as a breakthrough and novelty. In other words, we seek to study what childhood can be, not only for children but for people of all ages. How can the relationship between children, philosophizing, thinking, and dreaming be addressed? Often, we the project participants are surprised by the curiosity stimulated by sharing and telling our stories. We will aim to recover remarkable experiences in order to analyze the power of philosophy in overcoming boundaries, becoming childish, inviting to dream, and transforming lives.